La Pena de Muerte en los Delitos Sexuales de Violación - Carrión Carrión, Daniela Alejandra (2022)
The present thesis is entitled: "The death penalty in sexual crimes of rape", and its interest in developing is due to carry out a study in view that the violation of the right to sexual, reproductive and personal integrity has been committed within society, resulting in the reports of the State Attorney General's Office that an average of 14 rape complaints are received per day, among which are minors and that is why the application of the death penalty can be considered in the face of such a severe crime. The study carried out focuses more on sexual crimes, the same ones that are more frequent in women, resulting in surveys carried out by the National Institute of Statistics and Censuses of 25.7%; and in terms of data regarding men, they do not provide us with statistical data , and on many occasions it becomes gender-based, leading to an imbalance of the legal norms that could support the protection of personal and sexual integrity, which is why a criminological study can be considered for said sanction, taking into account that there are legal rules and treaties that do not give way or a positive response to this application. In this thesis, materials and methods were applied that allowed the development of the investigation, Likewise, interviews and surveys were carried out with legal professionals, the results of which served to propose the project in which the reform for an application of the maximum penalty would be taken into consideration, validating the aforementioned about the legal regulations that do not allow the application of the death penalty, which is why the reform of article 171, paragraph 1, of the Comprehensive Criminal Organic Code, which sets out the sanctions for the crime of rape, would be carried out.